The Relationship Between Patient Knowledge, Family Support, and Treatment Supervisors with Tuberculosis Medication Adherence - Muhammad Romadhon; Yazika Rimbawati; Miranda Sari (CV. AFDIFAL MAJU BERKAH, 2026)
Tuberculosis remains a major public health problem globally and in Indonesia, with medication adherence playing a crucial role in treatment success and prevention of drug resistance. Non-adherence to tuberculosis treatment contributes to treatment failure, disease recurrence, and ongoing transmission. Previous studies have indicated that individual, familial, and supervisory factors influence adherence; however, evidence from primary healthcare settings remains limited. This study aimed to examine the relationship between patient knowledge, family support, and treatment supervisors with tuberculosis medication adherence among pulmonary tuberculosis patients in a primary healthcare setting. A quantitative cross-sectional study was conducted in the working area of UPTD Puskesmas Kemalaraja, Ogan Komering Ulu Regency, Indonesia, in July 2025. The study population consisted of 34 pulmonary tuberculosis patients, and total sampling was applied. Data were collected through structured interviews using validated questionnaires measuring medication adherence, patient knowledge, family support, and the role of treatment supervisors. Univariate analysis was used to describe variable distributions, while bivariate analysis was performed using the Chi-square test with a significance level of 0.05. The findings showed that most patients had moderate medication adherence (47.1%). Patient knowledge was predominantly at a moderate level (52.9%), family support was mostly high (50.0%), and treatment supervisor involvement was largely high (58.8%). Statistical analysis revealed significant associations between patient knowledge and medication adherence (p = 0.003), family support and medication adherence (p = 0.022), and treatment supervisors and medication adherence (p = 0.039). Patient knowledge, family support, and treatment supervisors were significantly associated with tuberculosis medication adherence. Higher knowledge levels, strong family support, and active treatment supervision were linked to better adherence outcomes.